Corporate Culture: A positive correlate with marketing effectiveness - Norburn, David; Birley, Sue; Dunn, Mark G. (Cranfield School of Management, 1984)
This study tests the relationship between the Peters and Waterman cultural criteria of customers closeness and corporate values, to scales of marketing effectiveness as developed by Kotler. Analysis of data collected from 54 mid-American companies suggests a positive association. Marketing effective companies appear to have distinguishing cultural profiles when compared to marketing ineffective companies.
Presented at Strategic Management Conference, Barcelona, Spain, October 1985